Rojstva in samomori v Sloveniji skozi tri desetletja (1971-2001) - Cukut Krilić, Sanja (ZRC SAZU, Založba ZRC, 2006)
In Slovenia, quite a few researchers have studied fertility and suicide, but rarely have the connections between both phenomena been made. The author aims to overcome simplified explanations of falling fertility and rising suicide rates by studying population dynamics as a socially relevant issue both at the Slovenian as well as the global level. She studies fertility and suicide by focusing on the historical development of population issues, recent theoretical population analyses and demographic statistics. Fertility and suicide are analysed from the viewpoint of approaches developed in the social sciences and humanities. In the second part of the monograph, these approaches are applied to fertility and suicide trends in Slovenia and press media reports on both issues.By providing an overview of the history of studying fertility and suicide in Slovenia and abroad, the author has concluded that most approaches to fertility and suicide are grounded on the premises of the modernisation theory. Nevertheless, she was not discouraged to study alternative approaches to fertility and suicide that, according to researchers in the humanities, do not necessarily have a lower explanatory potential.